Respons Pertumbuhan dan Produksi Cabai Merah (Capsicum annuum L.) terhadap Aplikasi Pupuk NPK 16:16:16 dan Pupuk Organik Urin Kelinci: Response of Growth and Production of Red Chili (Capsicum annuum L.) to the Application of NPK 16:16:16 and Rabbit Urine Organic Fertilizer - Rismayanti, Andra; Rosmala, Arrin; Lestari, Peni (Jurnal Hortikultura Indonesia, 2024)
Liquid organic fertilizer, known as POC, is a biological fertilizer acts as complementary to inorganic fertilizers due to its capacity to enhance the physical, chemical, and biological properties of the soil. This research aims to assess the growth and production response of red chilies (Capsicum annuum L.) to the application of NPK 16:16:16 fertilizer combined with rabbit urine-based POC. The experimental design employed a non-factorial Randomized Block Design (RAK) with five treatments and six replications. Chili cultivation took place in open fields using polybags. The results indicated that the application of NPK 16:16:16 fertilizer, rabbit urine-based POC, and a combination of both did not show significant differences during the vegetative phase of the plants but did impact yield components. Rabbit urine-based POC 50% (by water) potentially substitute 20% of NPK 16:16:16 fertilizer dossage application. The combination of NPK 4 g polybag-1 + POC 50% (P2) produced the highest yield component results and was equivalent to NPK 5 g polybag-1 + POC 50% (P3). Further research is necessary to determine the optimal concentration and dose of rabbit urine-based POC for chili cultivation in polybags. Keyword: red chilies, yield components, biological organic fertilizer